Training in note making : the effects of a training scheme on first year teacher-training students - Ferreira, Ignatius Leopold (Rhodes University, Faculty of Education, Department of Education, 1992)
This research work is based upon a training technique devised and recommended by J. Smith (1985) in a pamphlet published by The British Historical Association. The technique involves training school pupils in the making of notes from text books and references and then selecting appropriate points to answer specific questions. The technique was slightly adapted and used on a small Experimental Group drawn from Black first year College of Education students at an Eastern Cape College. A Control Group from the same College received conventional lectures on two topicS from the first year college syllabus - the San and Khoi peoples of Southern Africa. The Experimental Group was given a brief training period in Smith's technique and then worked independently on extended reading passages on the same topics. Both groups received a similar introduction of a video tape on the San and a slide presentation on the Khoi. Both groups wrote the same final test after their learning experiences were over and both groups completed questionnaires on the initial visual input and on their reactions to the learning experience. Comparisons are drawn between the results and the students' reaction to those learning experiences.
Keywords: Note-taking; Teachers -- Training of; Study skills